Reinventing the skilled region: Human capital externalities and industrial change - Daniel F. Heuermann (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2009)
Bridging the gap between the literatures on industrial change and human capital externalities we investigate the complementarity between aggregate regional education and job turnover. On the level of regional industries in Germany we find strong evidence for such complementarity. Thus, regional human capital turns out to be a crucial ingredient for productivity enhancing industrial change, while human capital externalities arise first and foremost in dynamic labor markets. On the firm level, we find human capital externalities to accrue predominantly to growing firms which benefit from sharing, matching, and learning externalities arising from a large supply of highly qualified workers in skilled, dynamic labor markets. Despite the joint impact of human capital and industrial change on productivity, we find only weak evidence that inter-industry differences the job turnover of highly qualified workers shape the geography of industry location across regions.
Keywords: D62; J24; R11; R12; 330; Human Capital Externalities; Job Turnover; Industrial Change